Changing Ties in a Far-Flung, Multidisciplinary Research Network: The Case of GRAND. (May 2015) - Dimitrova, Dimitrina; Mok, Diana; Wellman, Barry
We study a multidisciplinary, geographically dispersed, and multi-institutional research network that shows the complex relationships in collaborative research. Although collaborative work ties declined, the number of friendship and advice ties stayed stable and acquaintanceship ties grew. Most researchers seem satisfied with the network and relish the opportunities for cross-disciplinary exchanges. The benefits of the network do not lie in the traditional academic output of publications and artifacts, but in intellectual exchanges, knowledge transfer, fostering long-term ties within and across disciplines and universities, and the development of a collaborative culture.